2021
DOI: 10.1002/trc2.12171
|View full text |Cite
|
Sign up to set email alerts
|

An international, randomized, placebo‐controlled, phase 2b clinical trial of intepirdine for dementia with Lewy bodies (HEADWAY‐DLB)

Abstract: Introduction A phase 2b clinical trial, HEADWAY‐DLB, was performed to assess treatment with intepirdine, a serotonin receptor antagonist, in patients with dementia with Lewy bodies (DLB). Methods HEADWAY‐DLB was a multinational, double‐blind, randomized, placebo‐controlled study. Two hundred sixty‐nine DLB patients were randomized to receive placebo, 70 mg/day intepirdine, or 35 mg/day intepirdine over 24 weeks. The primary endpoint was change from baseline to week 24 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…22 Landipirdine and intepirdine were evaluated for their potential benefits in Parkinson's disease dementia and dementia with Lewy bodies, respectively. 23,24 No benefits were observed in either disease population. Overall, inconsistent treatment effects were observed on cognition with 5-HT 6 receptor antagonists when tested as a standalone treatment or as an adjunct to cholinesterase inhibitors.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…22 Landipirdine and intepirdine were evaluated for their potential benefits in Parkinson's disease dementia and dementia with Lewy bodies, respectively. 23,24 No benefits were observed in either disease population. Overall, inconsistent treatment effects were observed on cognition with 5-HT 6 receptor antagonists when tested as a standalone treatment or as an adjunct to cholinesterase inhibitors.…”
Section: Introductionmentioning
confidence: 93%
“…Another 5‐HT 6 receptor antagonist, PF‐05212377 (SAM‐760), was evaluated for its potential benefits on cognition in patients with mild to moderate AD dementia and neuropsychiatric symptoms but its study was terminated after an interim analysis showed no benefits on cognition or neuropsychiatric symptoms 22 . Landipirdine and intepirdine were evaluated for their potential benefits in Parkinson's disease dementia and dementia with Lewy bodies, respectively 23,24 . No benefits were observed in either disease population.…”
Section: Introductionmentioning
confidence: 99%
“…The UPDRS is responsive to therapeutic interventions and is the reference scale for regulatory agencies [ 156 , 157 ]. Moreover, it has been used as a primary outcome in DLB trials targeting motor function [ 99 , 158 ]. The MDS-UPDRS is a newer version that differs from the UPDRS especially in the evaluation of non-motor aspects of PD [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…66 In addition to these active disease-modifying trials, numerous trials of symptomatic therapies with diverse mechanisms of action are completed or underway (Table 4). Unfortunately, many of these studies, including the recently published HEADWAY-DLB trial, 67 showed no clear efficacy, although peer-reviewed publications for several studies remain lacking. While disappointing, these trials demonstrate that clinical trials in DLB are feasible, including in international settings.…”
Section: Managementmentioning
confidence: 99%
“…While disappointing, these trials demonstrate that clinical trials in DLB are feasible, including in international settings. 67 Recently, the AscenD-LB study (NCT04001517) met its primary objective of improving cognition in individuals with DLB and a phase III study is planned. 68…”
Section: Managementmentioning
confidence: 99%